Domain Names and Trademarks: Law Enforcement Issues - N. A. Permyakova (Сибирское юридическое обозрение, 2015)
The article discusses the aspects of legal regulation of domain names, their relationship with trademarks and other means of individualization. Judicial practice of consideration of disputes between trademark owners and domain name holders is under study.